2014
DOI: 10.1002/mds.25922
|View full text |Cite
|
Sign up to set email alerts
|

The Huntington's disease dysphagia scale

Abstract: We developed a valid and reliable 11-item scale to measure the severity of dysphagia in Huntington's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
(42 reference statements)
1
12
2
Order By: Relevance
“…In fact, despite dysphagia is a frequent and potentially invalidating symptom in HD patients, its assessment is not included in the current clinical evaluation of this condition. A recent study stated the validity of a questionnaire for patients and caregivers in detecting this aspect of HD [13] . However, the cognitive decline and the behavioural disturbances characterising HD patients may reduce the reliability of a self-reported scale, and in fact, in that study, a low agreement between patients and caregivers emerged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, despite dysphagia is a frequent and potentially invalidating symptom in HD patients, its assessment is not included in the current clinical evaluation of this condition. A recent study stated the validity of a questionnaire for patients and caregivers in detecting this aspect of HD [13] . However, the cognitive decline and the behavioural disturbances characterising HD patients may reduce the reliability of a self-reported scale, and in fact, in that study, a low agreement between patients and caregivers emerged.…”
Section: Discussionmentioning
confidence: 99%
“…The DOSS, preceded by BSAS, indicated that dysphagia is a prevalent motor symptom of HD, specially correlated with global motor slowness and impairment of mouth-tongue motor control. The concordance with the HDDS questionnaire [13] may be further obtained, though the direct patient observation by SLTs should be provided in order to improve early diagnosis and treatment recommendations such as modification of diet. The major limitation of the study is its small group size, which is a frequent problem in rare disorders, while multicentre evaluations may confirm the significance of clinical correlations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worsening of neurological condition may cause an individual to become distracted and overwhelmed by mealtime activity. In 2014 Heemskerk et al developed a valid and reliable 11-item scale to measure the severity of dysphagia in HD [19]. This Swallowing Disturbance Questionnaire could be very helpful when making decision about referral to a speechlanguage therapist (SLT) and further assessment including clinical observation for signs of aspiration when different consistencies of food/liquids are consumed, or instrumental assessment like video fluoroscopy.…”
Section: Dysphagiamentioning
confidence: 99%
“…For example, a recent 11-item scale developed to assess dysphagia in HD [17] evaluates the presence or absence of dysphagia-related problems such as drooling, nasal regurgitation, coughing, and choking. However, this scale does not the affect that dysphagia has on quality of life.…”
mentioning
confidence: 99%